PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI BADAN PERENCANAAN, PENELITIAN, DAN PENGEMBANGAN DAERAH SURAKARTA - Citra Agil Romadhona, Djumali & Sri Hartono (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2018)
The purpose of this study is 1) to determine the influence of leadership, work motivation and work environment simultaneously on employee performance. 2) To know the influence of leadership on employee performance BAPPEDA Surakarta. 3) To determine the effect of motivation on employee performance of BAPPEDA Surakarta. 4) To know the effect of work environment on employee performance of BAPPEDA Surakarta. The population of this research is BAPPEDA Surakarta employees, amounting to 45 people. Because the number of population is 45 people then the technique in this study using census method, the sample in this study is 45 respondents. Data analysis using multiple linear regression, t test, F test and coefficient of determination (R2). The result of t test analysis is known that leadership variable has a significant influence on performance. Motivation variable has a significant influence on performance. Environmental variables have a significant effect on performance. The result of F test analysis is known that leadership, motivation, and environment variables together have influence on performance. The result of determination coefficient analysis is known Adjusted R square (R2) of 0,508, it shows that leadership variable (X1), motivation (X2), and environment (X3) have influence to performance equal to 50,8%. While the rest (100% - 50,8% = 40,2%) is influenced by other factors outside the variables studied.Kaywords: Leadership, motivation, environment, performance